Limitations of diamondoids in the quantitative evaluation of petroleum cracking in ultra-deep carbonate reservoirs of the Shunbei area, Tarim Basin - Qianru Wang; Haiping Huang; Jiyuan Sun; Jiajun Huang; Tao Jiang (Frontiers in Marine Science, 2025)
Diamondoid hydrocarbons have been widely used to assess the extent of petroleum thermal cracking. In reservoirs subjected to multi-stage petroleum charges, thermal cracking might not occur in situ and, therefore, complicate the accurate evaluation of cracking within a petroleum mixture. The Shunbei area in the Tarim Basin is typical of ultra-deep carbonate reservoirs with multi-stage tectonic movements and petroleum charges where thermal cracking and evaporative fractionation are common. This study takes oil samples from the No.1 and No.5 fault zones in the Shunbei carbonate reservoirs as a case study to investigate the limitations of using diamondoid hydrocarbons for evaluating petroleum thermal cracking in reservoirs where diamondoid-rich gas has intruded. Organic geochemical data reveal that the abundant diamondoids in the No.1 fault zone were allochthonous, while the less abundant diamondoids in the No.5 fault zone are from in situ thermal cracking. These findings suggest that diamondoids may provide misleading indications of oil cracking, as they can be contaminated by allochthonous cracked oils. Therefore, caution should be taken when diamondoid hydrocarbons are applied to evaluate thermal cracking. Novel indicators remain to be proposed to more accurately assess the degrees of in-reservoir oil cracking with petroleum mixing from a secondary, diamondoid-rich charge.